Fluctuation of Asymmetry of Hybrid Cantang Grouper (Epinephelus fuscoguttatus x Epinephelus lanceolatus) Originating from Situbondo and Bali - Lailatul Lutfiyah; Darmawan Setia Budi (Journal of Aquaculture Science, 2019)
Asymmetric fluctuations function as a measure of organ stability in pairs in an individual. This study aims to determine the value of asymmetric fluctuations in hybrid grouper hybrid fish from Situbondo and Bali. The study was conducted for 3 months, starting from July-September 2018. The grouper used in this study was 100 individuals from each region, with a size of 7-9 cm. Bilateral meristic characters measured include the pectoral fin, ventral fin and lateral line. The results showed that the ventral fin character of the grouper fish from Situbondo and Bali had a higher FA value of 0.6-0.7, while the lateral linea organ had a higher FAm value, 1.1 to 1.9. The FAgb value of the grouper originating from Situbondo has a high value compared to the grouper from Bali, which is 1.5-2.4.